Penerapan Media Kantong Bilangan dalam Materi Pengurangan untuk Meningkatkan Hasil Belajar Siswa Kelas 3 SDN Karangasem 1 Surakarta: Penelitian - Scholastica Irene Ratri Primativa; Asna Fura Eda; Vira Yunita; Ika Candra Sayekti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to improve student learning outcomes through number bag media in mathematics subjects on subtraction material with borrowing techniques for grade 3 elementary school. This study uses a classroom action research method with pretest and posttest data collection techniques, as well as documentation. This classroom action research was conducted to address the gap in student learning outcomes in subtraction material with borrowing techniques in grade 3 elementary school in Surakarta. The study consisted of two cycles, each of which included the planning, implementation, observation, and reflection stages. Pre-research was conducted through discussions with teachers and analysis of student scores. The main objective was to test the effectiveness of number bag media in helping students understand subtraction material. The results showed that the use of number bag media can improve students' understanding by 85.10% on subtraction material with borrowing techniques. They showed a satisfactory increase in scores after following cycles 1 and 2.